Strategi Komunikasi Dinas Kesehatan Melalui Penerbitan Sertifikat Pangan Industri Rumah Tangga (PIRT) dalam Meningkatkan Taraf Kesehatan Masyarakat di Kota Bukittinggi - Lara Dwiana (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2021)
The communication strategy carried out by the Bukittinggi City Health Office in improving the level of public health in Bukittinggi City is carried out in the form of health counselling with the aim of issuing a Household Industry Food Certificate (PIRT). To describe this research using the theory of behaviorism, wherein in this theory of behaviorism, learning is a change in behaviorism as a result of the interaction between stimulus and response, This study used qualitative methods to describe communication strategies through health counselling, while data collection techniques used observation, interviews, and documentation. and using purposive sampling techniques by determining informants of certain criteria that support the objectives of the study. The informants who are in accordance with these criteria are Kasi and SDK staff of the Bukittinggi City Health Office because they are the persons responsible for the planning and implementation of PIRT activities in the work area of the Bukittinggi City Health Office and the people of Bukittinggi City who participated in the Food Safety Counselling (PKP) to obtain PIRT certificates. The results of this study show the application of communication strategy measures carried out by the Bukittinggi City Health Office through the issuance of Household Industry Food certificates (PIRT), namely: selecting audiences and setting communicators; setting target targets; compiling messages; and carrying out evaluation activities. However, after conducting a SWOT analysis, there were shortcomings encountered, namely that the Bukittinggi City Health Office did not use media in disseminating information and the lack of health workers in the SDK section of the Bukittinggi City Health Office